A survey of knowledge, attitude, and practices of private retail pharmacies staff in tuberculosis care: study from Dera Ismail Khan City, Pakistan - Tehmina Mustafa; Yasir Shahzad; Ayyaz Kiani (Taylor & Francis Group, 2018)
Background In order to engage pharmacies in tuberculosis (TB) care, a survey was conducted in the Dera Ismail (DI) Khan City of the Khyber Pakhtoon Khwa province, Pakistan. The objectives were to; 1) characterize the retail pharmacies; 2) determine knowledge of the staff on various aspects of pulmonary TB; 3) determine practices related to the sale of anti-TB drugs, and referrals of presumptive TB patient, and willingness to participate in the National Tuberculosis Control Programme's (NTP) Directly Observed Treatment Short-Course (DOTS) strategy. Methods A cross-sectional survey was conducted by using a structured questionnaire to collect data from pharmacy staff at all the private retail pharmacies of the DI khan city. Results All the interviewed staff (n = 82) were males, only 38% had formal training as pharmacist (5%) or as a pharmacy assistant (33%). Pharmacies established for a longer period were better staffed and had high customer load. About 92% of the interviewed staff knew that persistent cough is a symptom for TB, 82% knew that TB is diagnosed by examination of sputum. Almost 66% of the pharmacy staff did not know multi-drug resistance TB as a consequence of improper treatment. Those with formal training and longer experience in retail pharmacy had better knowledge of various aspects of TB as compared to the staff with no formal pharmacy training and lesser experience (p < 0.01). Only 57% were aware of NTP while only 30% had heard of the DOTS strategy. All reported sale of first-line TB drugs as fixed dose combinations. The majority (80%) referred presumptive TB patients to chest physicians and no patient was referred to the NTP. Nearly 83% of the interviewed staff was willing to be involved in TB control efforts by getting training and referring patients to the DOTS facility. Conclusion There was shortage of professionally qualified and female staff in private retail pharmacies. Knowledge of professionally qualified staff about TB seemed sufficient to identify presumptive TB patients; however, their knowledge about NTP and DOTS was poor, and referral practices to NTP and DOTS centers were suboptimal. Majority of staff was willing to be involved in TB control efforts.